Odpowiedzi

Najlepsza Odpowiedź!
2009-11-17T19:14:23+01:00
√27 + √12 + √75 - √108 = √9*3 + √4*3 + √25*3- √36*3= 3√3+2√3+5√3-6√3=4√3

∛3 * ∛9 + ⅖ : √3⅗ =³√27+²/₅ ÷√¹⁸/₅=3+²/₅÷√18/√5=3+²/₅*√5/√18=
=3+2√5/5√18

(0,9)⁴ * (1¹/₉)⁴ - (1,6)³ : (0,8)³ =(0,9*¹⁰/₉)⁴-(1,6:0,8)³=1⁴-2³=1-8=-7

równanie : x + y = 144
0.25x = 0,5y

x+y=144
0,25x=0,5y /*4
x+y=144
x=2y
2y+y=144
3y=144 /:3
y=48
x+48=144
x=144-48
x=96

x=96
y=48
1 5 1
2009-11-17T19:19:10+01:00
√27+√12+√75-√108 =√9*3+√3*4+√3*25-√36*3=3√3+2√3+5√3-6√3=4√3

∛3 * ∛9 + ⅖ : √3⅗ =∛27+2/5:∛3⁵=3,4:∛243=3,4:∛27*9=3,4:3∛9=3,4*3∛9/3∛9*3∛9=10,2∛9/9*∛81=10,2∛9/9*∛27*3=10,2∛9/27∛3

(0,9)⁴ * (1¹/₉)⁴ - (1,6)³ : (0,8)³=(9/10-10/9)⁴-(0,8)³=(81/90-100/90)⁴-0,512=(-19/90)⁴-0,512=130321/65610000-0,512=130321/65610000-512/10000=130321/65610000-3359232/65610000=-3228911/65610000

x+y=144
0,25x=0,5y/:0,25
x+y=144
x=2y
2y+y=144
x=2y
3y=144/:3
x=2y
y=48
x=96